Wetland use by brood‐rearing female ducks in a boreal forest landscape: the importance of food and habitat. (6th December 2012) - Nummi, Petri; Paasivaara, Antti; Suhonen, Sari; Pöysä, Hannu
Abstract : Habitat use by birds may be related to single or interacting effects of habitat characteristics, food resources and predators, but little is known about factors affecting habitat use by wetland species in boreal ecosystems. We surveyed brood‐rearing females and ducklings of four common boreal duck species to assess the effects of habitat structure and food resources on the use of wetlands by brood‐rearing ducks. Although wetland use by duck broods was related to habitat structure and food abundance, their relative importance varied among duck species. For the Common Goldeneye Bucephala clangula, a diving duck, aquatic invertebrates and large emerging insects were the most important factors associated with wetland use. Common Teal Anas crecca broods were observed more often on wetlands with greater Dipteran emergence, whereas in Mallard Anas platyrhynchos both habitat structure and large emerging insects were important. The occurrence of Eurasian Wigeon Anas penelope broods was related to emerging Diptera and habitat structure but the associations were not strong. The varying habitat and food requirements of common duck species could influence the success of wetland management programmes, and consideration of these factors may be particularly important for initiatives aimed at harvested species or species of conservation concern.